Detrimental effects of online pro-eating disorder communities on weight loss and desired weight: Longitudinal observational study - Feldhege, Johannes; Moessner, Markus; Bauer, Stephanie (Journal of medical internet research, 2021)
Background: Online pro-eating disorder (pro-ED) communities are considered harmful because of their detrimental effects on their users’ body dissatisfaction, dieting, and help seeking. To date, it is unknown to which extent participation in pro-ED communities affects users’ body weight and desired weight loss. - Objective: This study aims to investigate the changes in the current and desired body weight of users of a pro-ED community (r/proed) on the social media website Reddit over time. - Methods: Data on 1170 users and the unsolicited weight information they shared with the pro-ED community were collected over a period of 15 months. Linear growth models were used to model changes in the users’ current and desired BMI over time. - Results: Both current and desired BMI decreased over time, with a predicted rate of 0.087 and 0.015 BMI points per week, respectively. Weight loss was moderated by the users’ activity level in the community, with more active users losing more weight. Users with a higher baseline BMI experienced greater weight loss, but even users with a very low baseline weight (BMI <17 kg/m2) lost weight during their participation. In addition, users decreased their desired weight over time, with many pursuing extremely low, unrealistic weight goals. Changes in the desired weight were moderated by the baseline current BMI and baseline desired BMI. Users with higher desired weight and lower body weight at baseline decreased their desired weight more over time. - Conclusions: This is the first study to demonstrate the detrimental effects of pro-ED communities in a longitudinal study based on a large data set of user-generated online data. The results extend the literature detailing the harmful effects of online pro-ED communities by showing users’ weight loss, decreases in desired weight, and that higher activity levels lead to greater weight loss. Users could be driven to pursue very low, unrealistic weight loss goals by images of very thin bodies presented in these communities
Gesehen am 12.11.2021